Divergent Synthesis of Isochroman-4-ols, 1,3-Dihydroisobenzofurans, and Tetrahydro-2H-indeno[2,1-b]furan-2-ones via Epoxidation/Cyclization Strategy of (E)-(2-Stilbenyl/Styrenyl)methanols - Jongcharoenkamol, Jira; Jancharoen, Kitsana; Batsomboon, Paratchata; Ruchirawat, Somsak; Ploypradith, Poonsakdi (Synthesis, 2023)
Starting from (E)-(2-stilbenyl/styrenyl)methanols, two distinct scaffolds, namely isochroman-4-ols and 1,3-dihydroisobenzofurans (phthalans), could be synthesized via an epoxidation/cyclization strategy. Indenes, readily accessible from the same starting materials, could undergo epoxidation/ring-opening/cyclization to provide tetrahydro-2H-indeno[2,1-b]furan-2-ones. Stilbene/styrene/indene epoxidation by m-CPBA or DMDO converted the nucleophilic olefin into the electrophilic epoxide, which subsequently underwent the regioselective ring-opening either by the hydroxy or the ester group to furnish the corresponding products with stereocontrol at the newly formed stereogenic centers. The reaction proceeded under substrate control to yield each product type exclusively.
Keywords: epoxidation; cyclization; carbocation; fused-ring systems; stereoselectivity